Lactic Acid Bacteria in Chinese Sauerkraut: Its Isolation and In Vitro Probiotic Properties - Ming-Yang Han; Wen-Yong Lou; Meng-Fan Li (Foods)
Probiotics have been widely explored for their potential in managing hyperuricemia. However, their isolation and identification are fundamental prerequisites for practical application. In this study, 254 lactic acid bacteria (LAB) strains were isolated from Chinese sauerkraut and screened for probiotic potential based on genomic and phenotypic characteristics, as well as nucleoside-degrading activity relevant to decrease serum urate. Among them, Lactiplantibacillus plantarum (L. plantarum) F42 exhibited the highest bile salt tolerance (survivor rate: 19.46 ± 4.33%), strong adhesion to Caco-2 cells (1.89 ± 0.12%), effective nucleoside degradation (inosine: 5.46 ± 0.67 mg∙L−1∙min−1; guanosine: 3.84 ± 0.11 mg∙L−1∙min−1), and notable anti-listeria activity (inhibition zone: 6.9 ± 0.3 mm). Based on its functional profile, L. plantarum F42 was selected as a promising probiotic candidate for further investigation of its urate-lowering effects. This work provides a new insight into anti-hyperuricemia probiotic selection based on in vitro nucleoside-degrading activity.